Probation, mental health and the Criminal Justice System: an introduction - Sirdifield, Coral (Probation, mental health and criminal justice, 2023)
This chapter introduces what probation is and provides an overview of the range of topics and perspectives included within the book. Key topics covered in the collection include the prevalence of mental health disorders in probation populations; the available evidence on the effectiveness of interventions to address mental health disorders, substance misuse and suicidality in probation populations; findings from recent inspection work; mental healthcare initiatives that have developed within probation to offer psychological interventions and reduce suicides; working with people with autism; methodological challenges when conducting research around mental health and probation; the value of co-production; and how probation may need to adapt in a post-pandemic world.